DEVELOPMENT OF A TECHNOLOGY FOR OBTAINING DRY EXTRACT WITH A TINCHING EFFECT - Tuychieva , Shakhodat (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
Research on the development of a technology for obtaining a dry extract containing flavonoids of the H. scabrum plant growing in the territory of the Republic of Uzbekistan is a pressing task. This article discusses the industrial technology for obtaining dry extract of coarse sorrel, in particular, the fractional composition of coarse sorrel raw materials ground in mills with various sieves, the indicators of influencing factors, the use of a spray drying device in obtaining dry extract of coarse sorrel, as well as the naturalness, low side effects, and biological compatibility of preparations obtained from plant raw materials, their advantages of wide application in medical practice.